As relações entre professores dos ciclos I e II do ensino fundamental - Deu, Marcia Eleane Braghini Deus (2007)
This study answers the following question: What are the elements which characterize the relationships among the teachers of both cycles of the primary school (1st to 4th grades and 5th to 8th grades), in those teachers view, and how does this relationship interfere in the construction of their identities? The objective of the research consists of investigating the perceptions that teachers from both segments of the primary school have about themselves and about each other, about the role they perform at school, and the relationships they establish amongst themselves. The study has the hypothesis that the views/ perceptions that the primary school teachers from one cycle (1st to 4th grades) have about the teachers from the other cycle (5th to 8th grades) contribute to the remoteness or the approach among them, with consequences in their view on the educational work accomplished in both cycles. Some authors supply theoretical reference for the study, such as: J. Gimeno Sacristán, (concept of practice/ pedagogical action); A. Pérez Gómez and L. Brunet (culture, school culture and educational culture); M. Tardif, A. Hargreaves, M. Apple and others (professionalization, knowledges and educational work); C. Dubar (identity construction) and P. Berger and T. Luckmann (reality interiorization and identity formation). It is a research of qualitative nature, analytical descriptive of the teachers perception regarding the relationships amongst themselves and about their own work, by means of dynamics with characteristics of Focus Group, accomplished in meetings with 40 Primary School teachers (from both cycles) of two state public schools at a municipal district of the area of São Paulo, gathered in three groups. The meetings were recorded in audio and video and the data obtained were transcribed, organized in synthesis charts of depositions, whose analyses seek the elements capable to elucidate how the teachers see themselves; how they see each other and the work they accomplish; what they say about the relationships among them and which role they attribute to the school and the school system